Design of Risk Management in SPBE Infrastructure Based on PAN-RB Ministerial Regulation Number 5 of 2020 (Case Study: XYZ Institution) - Rochamwati, Rochmawati; Salman, Muhammad (Universitas Negeri Padang, 2023)
The arrival of the Industrial Revolution 4.0 not only spurred the acceleration of digitalization in industry and manufacturing, but also brought a broader influence to various sectors, including the government sector. One of the Government's efforts to support digital transformation is the issuance of Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems (SPBE). However, the application of SPBE in Central Agencies and Regional Governments can create a number of risks that will affect the achievement of SPBE objectives. Therefore, the Ministry of State Apparatus Empowerment and Bureaucratic Reform (PAN-RB) issued a PAN-RB Ministerial Regulation Number 5 of 2020 which contains SPBE Risk Management Guidelines that need to be implemented by SPBE organizers in managing SPBE risk in their respective agencies, including XYZ Work Unit. The XYZ Work Unit is one of the work units in the ABC Agency which is responsible for carrying out tasks and functions in the IT field. An SPBE risk assessment has been carried out on the SPBE Infrastructure in the XYZ Work Unit. From this research, 47 negative SPBE risks were obtained, of which 26 SPBE risks were above the SPBE Risk Appetite threshold so that recommendations for handling SPBE risk were then prepared based on the PAN-RB Ministerial Regulation Guidelines Number 5 of 2020.